Kim Jong II's Leadership of North Korea - LIM, Jae - Cheon (Routledge, 2009)
Kim Jong Il came to power after the death of his father Kim Il Sung in 1994. Contrary to expectations, he has succeeded in maintaining enough political stability to remain in power. Kim Jong Il's Leadership of North Korea is an examination of how political power has been developed, transmitted from father to son, and now operates in North Korea